PENGGUNAAN GENERATIVE ARTIFICIAL INTELLIGENCE DALAM ENAM TUGAS MANAJEMEN KEBENCANAAN MAHASISWA PENDIDIKAN GEOGRAFI UNIVERSITAS NEGERI MEDAN - Balqis, Anisah; Novira, Nina (Jurnal Samudra Geografi, 2025)
The study was intended to identify the application of artificial intelligence by the University of Medan University geography students in completing the application of the management of disaster lecture. The study is conducted in geography education at November-December University, 2023. The population in this study of geography education students who took the management course of disaster with the sample in this study is student batch 2021 who took the disaster management course. Data collection techniques are done with questionnaires and observation. The data-analysis technique is qualitative descriptive. Research shows that: (1) the extent of application of artificial intelligence by a geography student in the completion of the six disaster management classes was 73.2%. Geography school students used artificial intelligence to carry out a daily task of 41 students (73.21%), critical book report (55%), critical journal review (CJR) as many as 26 (46%), idealized as many as 33 (59%), mini research as many as 33 (59%), and project as many as 28 students (50%).